2021
DOI: 10.3389/fped.2021.622753
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Markers in the Management of Pediatric Polytrauma: Current Role and Areas of Future Research

Abstract: Severe trauma is the most common cause of mortality in children and is associated with a high socioeconomic burden. The most frequently injured organs in children are the head and thorax, followed by the extremities and by abdominal injuries. The efficient and early assessment and management of these injuries is essential to improve patients' outcome. Physical examination as well as imaging techniques like ultrasound, X-ray and computer tomography are crucial for a valid early diagnosis. Furthermore, laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 150 publications
(184 reference statements)
0
6
0
Order By: Relevance
“…It must be emphasized that this study was focused on factors, such as the mechanisms of accidents, the preclinical course of traumatized children, and clinical parameters, to decide on the required imaging modality. However, there are biomarkers, such as interleukin-6 and troponin, which correlate with the injury severity after trauma in children [ 34 , 35 ]. Currently, it remains uncertain if these molecules are significantly elevated as early as minutes or a few hours after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasized that this study was focused on factors, such as the mechanisms of accidents, the preclinical course of traumatized children, and clinical parameters, to decide on the required imaging modality. However, there are biomarkers, such as interleukin-6 and troponin, which correlate with the injury severity after trauma in children [ 34 , 35 ]. Currently, it remains uncertain if these molecules are significantly elevated as early as minutes or a few hours after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Forty 4-week-old young rabbits (as infant for average human weaning stage for 6 months) ( 1 ) weighing between 0.9–1.0 kg were randomly assigned into four groups: control, 0-h (h), 24 h, and 72 h (each group of rabbits was assessed only at the corresponding time after injury). Animals of both sexes were randomly grouped.…”
Section: Methodsmentioning
confidence: 99%
“…Road traffic injury presents a serious hazard to children, with traffic accidents accounting for 78% of severe injuries in this demographic, compared to 63% in adults ( 1 , 2 ). The distinction in seating postures between children and adults in motor vehicles contributes to the increased incidence of chest and abdominal injuries in children, reaching as high as 13%, surpassed only by head and neck injuries ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 Many of these studies have revealed that serum lactate is a reliable predictor of mortality in severely injured patients 4 , 6 , 7 and may even outperform arterial base deficit as a predictive tool. 8 , 9 Additionally, some smaller studies have indicated that both arterial and venous bicarbonate values can effectively predict mortality in critical care settings. 2 , 7 , 8 Serum bicarbonate and base deficit have been found to be approximately equivalent in their predictive capacity in other studies.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 7 , 8 Serum bicarbonate and base deficit have been found to be approximately equivalent in their predictive capacity in other studies. 7 Given that lactic acid measurements and arterial base deficit may not be immediately available at the time of a patient’s initial presentation, 9 further exploration of the predictive value of bicarbonate measures becomes critical.…”
Section: Introductionmentioning
confidence: 99%